2018
DOI: 10.2147/imcrj.s153099
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic reactions due to pantoprazole: case report of two cases

Abstract: BackgroundDrug-induced hypersensitivity reaction is of great clinical significance in therapeutics. The objective of this reporting of two cases is to show that anaphylaxis reaction can occur with pantoprazole.Case summariesA 38-year-old female reported to the emergency ward in a critical condition, with a history of periorbital edema, edema of the skin, pruritus, nausea, vomiting, and difficulty breathing 20 minutes after ingestion of a pantoprazole 40 mg tablet. A 32-year-old female reported to the emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Although some cases of post pantoprazole administration anaphylaxis (22,23) and edema (24,25) have been reported in humans, these clinical signs were not observed in our population. While the aim of this study was not to evaluate the clinical safety of pantoprazole in calves, the lack of observed adverse effects correlate with previously reported pantoprazole use in ruminants for case management of cattle (4,26), camels (27), sheep (15,28), yaks (29), and goats (30,31).…”
Section: Discussioncontrasting
confidence: 71%
“…Although some cases of post pantoprazole administration anaphylaxis (22,23) and edema (24,25) have been reported in humans, these clinical signs were not observed in our population. While the aim of this study was not to evaluate the clinical safety of pantoprazole in calves, the lack of observed adverse effects correlate with previously reported pantoprazole use in ruminants for case management of cattle (4,26), camels (27), sheep (15,28), yaks (29), and goats (30,31).…”
Section: Discussioncontrasting
confidence: 71%
“…Anaphylaxis has been reported in people after administration of pantoprazole tablets, manifesting as edema, pruritus, nausea, vomiting, respiratory distress, and rashes (13). In people, anaphylactic reactions have been observed with omeprazole, pantoprazole, and lansoprazole skin prick tests by one study, and the same study suggests that cross-reactivity may exist in people to proton pump inhibitors (14).…”
Section: Discussionmentioning
confidence: 97%
“…When used in humans for therapy, multiple adverse events have been reported from patients administered PPIs, mainly skin reactions, nephritis, pancytopenia, anaphylaxis, edema, hepatotoxicity, as well as biochemical changes such as hyponatremia and hypomagnesemia (8)(9)(10)(11)(12)(13)(14). Pantoprazole specifically has been associated with thrombocytopenia, hepatotoxicity, and pancreatitis (9,11,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In human patients, several adverse effects have been attributable to pantoprazole including anaphylaxis, thrombocytopenia and electrolyte disorders (27)(28)(29)(30)(31). While uncommon, these adverse effects also appear to be limited to geriatric human patients that undergo long-term therapy with pantoprazole (31).…”
Section: Discussionmentioning
confidence: 99%